Investigation of suitable spray drying conditions for sugarcane juice powder production with an energy consumption study - Khuenpet, Krittiya; Charoenjarasrerk, Nutcha; Jaijit, Sasarose; Arayapoonpong, Supha; Jittanit, Weerachet (Agriculture and Natural Resources, 2016)
Sugarcane juice was spray-dried under various conditions to determine the most suitable drying conditions for the manufacture of sugarcane juice powder. Initially, fresh, 30oBrix and 50oBrix sugarcane juice samples were dried in a laboratory-scale spray dryer at an air-drying temperature between 130 oC and 170 oC using maltodextrin, Arabic gum and dietary fiber as drying aids. It appeared that sugarcane juice should be concentrated under vacuum to 30oBrix and added with at least 15% maltodextrin before drying at 170 oC in order to obtain dried powder product with a low drying cost. After conducting the experiments in the laboratory, sugarcane juice powders were produced in a factory using an industrialscale spray dryer under five drying conditions. It was found that the energy cost of industrial-scale production of sugarcane juice powder ranged between 0.77 USD and 2.06 USD per kg of powder. According to the results of the industrial-scale experiments, the sugarcane juice powder should be produced using vacuum evaporation of the sugarcane juice to 30oBrix prior to adding maltodextrin at 30% by weight and then spray drying at 190 oC.